Evaluation of groundwater recharge based on rainfall and land use changes - Ebrahim, Mohammad Nazri (2020)
The soil water assessment tool (SWAT) is a continuous and distributed hydrologic model created to simulate the effect of land management practices on water in the watershed. Understanding relationship of water extraction of groundwater can lead to better watershed management. The main problem in this study is the complexity of recharge processes and limited observations in groundwater recharge in Malaysia makes it difficult to quantify. This study was done at Baung’s watershed (BW) which can be considered as an ungauged watershed. The estimation of groundwater recharge in BW was done using SWAT. A framework for SWAT input data including hydrography, terrain, land-use, soil and weather for BW was then focused in order to achieve the model simulation for ungauged basins. The results emphasize the importance and prospects of using accurate spatial input data for the physically based SWAT model. Normal rainfall condition, extreme-low rainfall condition, normal rainfall under future land use and extreme low rainfall condition under future in land-use development represented as Scenario 1, Scenario 2, Scenario 3 and Scenario 4 were evaluated in this study. These conditions give different groundwater recharge rate as different scenarios give different impact to groundwater. The coefficient of determination, R2 of the model is 0.9676. Model was found to produce a reliable estimation of groundwater recharge of 405 mm/year (14.6%), 194.12mm/year (11.1%), 214.23 mm/year (7.7%) and 95.55 mm/year (5.5%) for Scenario 1, Scenario 2, Scenario 3 and Scenario 4 respectively. In conclusion, it is suggested that groundwater recharge should not be assume with only one specific value such as 6%, 11% and 26% of annual rainfall as the land use development and rainfall intensity factors influencing groundwater recharge need to be took into consideration in assisting groundwater exploration and management.